Electromechanical Properties of Robocasted Barium Titanate Ceramics - Lorenz, Mylena Mayara; Martin, Alexander; Webber, Kyle Grant; Travitzky, Nahum (Advanced Engineering Materials, 2020)
This work presents the fabrication of dense polycrystalline barium titanate (BaTiO3, BT) for electromechanical transduction using robocasting and cold isostatic pressing (CIP). The use of CIP as post-treatment is proposed to eliminate defects and increase the density of robocasted parts to improve the piezoelectric performance. For robocasting, pastes containing 50 and 52 vol% are developed; the resulting green robocasted parts are CIPed at 100 and 150 MPa. Using this proposed technique, samples robocasted with BT52 and CIPed at 150 MPa display a relative density of approximate to 98%, comparable with reference polycrystalline samples. In addition, an increase in both the piezoelectric charge and voltage coefficient is observed in robocasted parts, with the values up to 195 pC/N and 12 x 10(-3) Vm N-1, respectively. These values, which are comparable with previous studies of polycrystalline BT, indicate that the combined robocasting and CIP technique is a possible method for producing 3D printed piezoelectric sensors.
CRIS-Team WoS Importer:2020-07-03